YOUNG CHARACTERISTICS OF PRIMARY CLASS STUDENTS AND THE METHODOLOGY OF FORMING THEIR MUSICAL KNOWLEDGE - Khojageldiyeva is the daughter of Mahfuza Ergash (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The article talks about mental development and behavioral characteristics during elementary school age. It was discussed how much attention should be paid to the age characteristics of students in music culture lessons.